VAN MERKEZ VE ÇEVRESİNİN HİDROJEOLOJİ İNCELEMESİ - AKDEMİR, SONER (Fırat Üniveristesi, 1997)
colored micritic limestone and volcanik rock includes basalt, andesitez, andesitic tuffs, dasitic dayk and diabaz. However, Kırkgeçit Formation which spreads out in large basins, is composed of old middle Eocene-Lower Miocene and includes conglomerate, sandstone and mudstone. Moreover, olistoliths belonging to different formations are present in the unit. The age of Lake Van Formation, which is represented in neatly arranged piles of loosly holded or non-holded clay, sand and small stone, is lake sedimentary of Plio- Kuaternary. The discord planes in the reqion developed in Laramian and Styrian Orogenic Phases. Discord plane was formed between Yüksekova Complex and Kırkgeçit Formation in Laramian Phase. With the effect of Styrian Phase, Kırkgeçit Formation become to the surface of water. Old Plio-Kuaternary lake sediments in Lake Van Formation covered Kırkgeçit Formation discordantly. The permeability of old Plio-Kuaternary Lake Van Formation is 1.8x1ü"4- 6.6x1ü"4 m/sn, permeability of Kırkgeçit Formation is 2.1xl0"7-3.3xl0"7 m/sn and finally permeability of alluvium is 1.8x1ü"4 m/sn. According to these results, Kırkgeçit Formation is an in permeable layer, Lake Van Formation and alluvium are permeable layers or they have low permeability. Water table map of the area under consideration were obtained for the Sebtember-1995 period. Distance between the lines decreases between Lake Van and Bakacik Village, and increases towards the inner parts of the plane. Permeability of the aquifer decreases and hydrolic slope increases where the lines are close to eac other, howewer, permeability of the aquifer increases and hydroclic slope discreoses where the distence between the lines is big. The slope of the unconfined aquifer in Van plane differs from 5.7xl0"3-6.4xl0"2. The direction of the groundwater is from east to west and it is discharged to Lake Van.colored micritic limestone and volcanik rock includes basalt, andesitez, andesitic tuffs, dasitic dayk and diabaz. However, Kırkgeçit Formation which spreads out in large basins, is composed of old middle Eocene-Lower Miocene and includes conglomerate, sandstone and mudstone. Moreover, olistoliths belonging to different formations are present in the unit. The age of Lake Van Formation, which is represented in neatly arranged piles of loosly holded or non-holded clay, sand and small stone, is lake sedimentary of Plio- Kuaternary. The discord planes in the reqion developed in Laramian and Styrian Orogenic Phases. Discord plane was formed between Yüksekova Complex and Kırkgeçit Formation in Laramian Phase. With the effect of Styrian Phase, Kırkgeçit Formation become to the surface of water. Old Plio-Kuaternary lake sediments in Lake Van Formation covered Kırkgeçit Formation discordantly. The permeability of old Plio-Kuaternary Lake Van Formation is 1.8x1ü"4- 6.6x1ü"4 m/sn, permeability of Kırkgeçit Formation is 2.1xl0"7-3.3xl0"7 m/sn and finally permeability of alluvium is 1.8x1ü"4 m/sn. According to these results, Kırkgeçit Formation is an in permeable layer, Lake Van Formation and alluvium are permeable layers or they have low permeability. Water table map of the area under consideration were obtained for the Sebtember-1995 period. Distance between the lines decreases between Lake Van and Bakacik Village, and increases towards the inner parts of the plane. Permeability of the aquifer decreases and hydrolic slope increases where the lines are close to eac other, howewer, permeability of the aquifer increases and hydroclic slope discreoses where the distence between the lines is big. The slope of the unconfined aquifer in Van plane differs from 5.7xl0"3-6.4xl0"2. The direction of the groundwater is from east to west and it is discharged to Lake Van.colored micritic limestone and volcanik rock includes basalt, andesitez, andesitic tuffs, dasitic dayk and diabaz. However, Kırkgeçit Formation which spreads out in large basins, is composed of old middle Eocene-Lower Miocene and includes conglomerate, sandstone and mudstone. Moreover, olistoliths belonging to different formations are present in the unit. The age of Lake Van Formation, which is represented in neatly arranged piles of loosly holded or non-holded clay, sand and small stone, is lake sedimentary of Plio- Kuaternary. The discord planes in the reqion developed in Laramian and Styrian Orogenic Phases. Discord plane was formed between Yüksekova Complex and Kırkgeçit Formation in Laramian Phase. With the effect of Styrian Phase, Kırkgeçit Formation become to the surface of water. Old Plio-Kuaternary lake sediments in Lake Van Formation covered Kırkgeçit Formation discordantly. The permeability of old Plio-Kuaternary Lake Van Formation is 1.8x1ü"4- 6.6x1ü"4 m/sn, permeability of Kırkgeçit Formation is 2.1xl0"7-3.3xl0"7 m/sn and finally permeability of alluvium is 1.8x1ü"4 m/sn. According to these results, Kırkgeçit Formation is an in permeable layer, Lake Van Formation and alluvium are permeable layers or they have low permeability. Water table map of the area under consideration were obtained for the Sebtember-1995 period. Distance between the lines decreases between Lake Van and Bakacik Village, and increases towards the inner parts of the plane. Permeability of the aquifer decreases and hydrolic slope increases where the lines are close to eac other, howewer, permeability of the aquifer increases and hydroclic slope discreoses where the distence between the lines is big. The slope of the unconfined aquifer in Van plane differs from 5.7xl0"3-6.4xl0"2. The direction of the groundwater is from east to west and it is discharged to Lake Van.

VI Declination and pumping experiments were carried out in unconfined aquifer. As a results of these experiments, permeability and conductivity of the aquifer were obtained 3.6xlQf4-l.3xlQr* m/sn, 1.09xl0-3-6.02xl0"3 m2/sn respectively. Storage coefficent and effective well interval differs from o^SxlO'M^SxlO"3 and from 35.55-177 m respectively. Kale group source discharges from limestone olistolits of Seske Formation in Kırkgeçit Formation, Kavurma-I, Kavurma-II and Bakacik sources discharges from Kırkgeçit Formation and Çoravanis source discharges from andesites in Yüksekova Complex. The most important source is the Kale group sources in the investigation area as being continously controlled and with long time disharge changes. Storage capacity of that source is 1.337xl05 m3 disharge period. Water in the area includes HC03, Ca and Mg ions. Salts such as Mg (HC03)2 and Ca (HC03)2 are mostly found in the gorundwater of that region. The source of Mg ion is in volcanic rocks in Yüksekova complex. CjS! and C3Sj salts are classified in ABD Salt Labaratory Graph and waters are in geod-fair classes. According to Schooner's "Diagram of Drinkable Waters" every springs and pumping waters except Kavurma-II spring are drinkable water classes in the region. Key Words: Van, hydorgeology, water chemical.colored micritic limestone and volcanik rock includes basalt, andesitez, andesitic tuffs, dasitic dayk and diabaz. However, Kırkgeçit Formation which spreads out in large basins, is composed of old middle Eocene-Lower Miocene and includes conglomerate, sandstone and mudstone. Moreover, olistoliths belonging to different formations are present in the unit. The age of Lake Van Formation, which is represented in neatly arranged piles of loosly holded or non-holded clay, sand and small stone, is lake sedimentary of Plio- Kuaternary. The discord planes in the reqion developed in Laramian and Styrian Orogenic Phases. Discord plane was formed between Yüksekova Complex and Kırkgeçit Formation in Laramian Phase. With the effect of Styrian Phase, Kırkgeçit Formation become to the surface of water. Old Plio-Kuaternary lake sediments in Lake Van Formation covered Kırkgeçit Formation discordantly. The permeability of old Plio-Kuaternary Lake Van Formation is 1.8x1ü"4- 6.6x1ü"4 m/sn, permeability of Kırkgeçit Formation is 2.1xl0"7-3.3xl0"7 m/sn and finally permeability of alluvium is 1.8x1ü"4 m/sn. According to these results, Kırkgeçit Formation is an in permeable layer, Lake Van Formation and alluvium are permeable layers or they have low permeability. Water table map of the area under consideration were obtained for the Sebtember-1995 period. Distance between the lines decreases between Lake Van and Bakacik Village, and increases towards the inner parts of the plane. Permeability of the aquifer decreases and hydrolic slope increases where the lines are close to eac other, howewer, permeability of the aquifer increases and hydroclic slope discreoses where the distence between the lines is big. The slope of the unconfined aquifer in Van plane differs from 5.7xl0"3-6.4xl0"2. The direction of the groundwater is from east to west and it is discharged to Lake Van.VI Declination and pumping experiments were carried out in unconfined aquifer. As a results of these experiments, permeability and conductivity of the aquifer were obtained 3.6xlQf4-l.3xlQr* m/sn, 1.09xl0-3-6.02xl0"3 m2/sn respectively. Storage coefficent and effective well interval differs from o^SxlO'M^SxlO"3 and from 35.55-177 m respectively. Kale group source discharges from limestone olistolits of Seske Formation in Kırkgeçit Formation, Kavurma-I, Kavurma-II and Bakacik sources discharges from Kırkgeçit Formation and Çoravanis source discharges from andesites in Yüksekova Complex. The most important source is the Kale group sources in the investigation area as being continously controlled and with long time disharge changes. Storage capacity of that source is 1.337xl05 m3 disharge period. Water in the area includes HC03, Ca and Mg ions. Salts such as Mg (HC03)2 and Ca (HC03)2 are mostly found in the gorundwater of that region. The source of Mg ion is in volcanic rocks in Yüksekova complex. CjS! and C3Sj salts are classified in ABD Salt Labaratory Graph and waters are in geod-fair classes. According to Schooner's "Diagram of Drinkable Waters" every springs and pumping waters except Kavurma-II spring are drinkable water classes in the region. Key Words: Van, hydorgeology, water chemical.
Hydrogeological investigation of the area the Van vicinity
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Jeoloji Mühendisliği; Geological Engineering